(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article describes methods of didactic learning support and effective teaching techniques that help improve foreign language teaching for students with special educational needs in higher education institutions. The need to use wellness technologies in teaching foreign languages in universities is also discussed.